Bis(N-isopropyl-N-methyldithiocarbamato-kappa S-2,S `)diphenyltin(IV) - Muthalib, A.F.; Baba, I.; Farina, Y.; Ng, S.W. (International Union of Crystallography, 2010)
The dithiocarbamate anions in the title compound, [Sn(C6H5)(2)(C5H10NS2)(2)], chelate to the Sn-IV atom, which is six-coordinated in a skew-trapezoidal-bipyramidal geometry. The molecule lies across a twofold rotation axis.